Supervisory nearly constant frequency hysteresis current control for active power filter applications in stationary reference frame - Fereidouni, Alireza; Masoum, Mohammad Sherkat; Smedley, K. (2016)
This paper proposes a new constant frequency space-vector hysteresis-band current control (CF-SVHCC) in the stationary reference frame (SRF) for three-level active power filter applications when applied to isolated neutral point (INP) systems. CF-SVHCC is designed based on two recognized modulation methods: 1) space-vector modulation and 2) adaptive hysteresis current control. The proposed technique consists of a simple circular hysteresis strategy around the current-error vector in SRF with the purpose of employing the zero- and nonzero-voltage vectors of the three-level voltage source inverter. CF-SVHCC continuously estimates an adaptive outer hysteresis-band in the SRF using the inverter switching signals by a simple and fast artificial neural network method called the adaptive linear neuron algorithm. The main part of CF-SVHCC is a supervisory control unit that operates in the SRF to avoid interphase dependency and systematically uses the voltage vectors associated with the estimated outer hysteresis-band to prevent a high switching frequency and, in turn, maintain the switching frequency constant. CF-SVHCC retains most benefits of the conventional HCC and also introduces additional advantages, including a constant switching frequency and the interphases independency in three-phase INP systems.